The effect of rowing to exhaustion on frontal plane angular changes in the lumbar spine of elite rowers - Wilson, F.; Gormley, J.; Gissane, C.; Simms, C. (Journal of Sports Sciences, 2012)
Lumbar spine injury is common in rowers and examination of spinal kinematics may improve the understanding of this injury's prevalence. This study aimed to examine the range of frontal plane angular displacement (AD) in the lumbar spine at L3 during ergometer rowing and to investigate the effect of exhaustion on lumbar kinematics. Twelve elite male rowers completed an incremental test on a Concept 2 ergometer. Lumbar AD at L3 was measured continually throughout the rowing trial using a Spectrotilt Inclinometer and blood lactate was sampled at 3-minute intervals. AD of between 4.7° and 8.8° was recorded at L3. There was a significant increase in AD between the first and last stage of the test (mean increase = 4.1 ± 1.94°, 95% Confidence Interval [CI], 2.9 to 5.3°, t = 7.36, P = 0.000014). Incremental rise in AD was associated with an incremental rise in blood lactate but regression confirmed that only stroke rate was a significant predictor for increasing angle. Thus there is a statistically significant increase in frontal plane AD at L3 over the course of an incremental exercise test although it cannot be confirmed if this is as a result of exhaustion. The values of AD confirm that there is motion in the frontal plane in ergometer rowing.